Southeastern Tropical Atlantic Changing From Subtropical to Tropical Conditions - Roch, Marisa; Brandt, Peter; Schmidtko, Sunke; Vaz Velho, Filomena; Ostrowski, Marek (Frontiers in Marine Science, 2021)
A warming and freshening trend of the mixed layer in the upper southeastern tropical Atlantic Ocean (SETA) is observed by the Argo float array during the time period of 2006–2020. The associated ocean surface density reduction impacts upper-ocean stratification that intensified by more than 30% in the SETA region since 2006. The initial typical subtropical stratification with a surface salinity maximum is shifting to more tropical conditions characterized by warmer and fresher surface waters and a subsurface salinity maximum. During the same period isopycnal surfaces in the upper 200 m are shoaling continuously. Observed wind stress changes reveal that open ocean wind curl-driven upwelling increased, however, partly counteracted by reduced coastal upwelling due to weakened alongshore southerly winds. Weakening southerly winds might be a reason why tropical surface waters spread more southward reaching further into the SETA region. The mixed layer warming and freshening and associated stratification changes might impact the marine ecosystem and pelagic fisheries in the Angolan and northern Namibian upwelling region.